Detection of apple firmness with a novel loudspeaker-based excitation device - Ding, Chengqiao; Wang, Dachen; Feng, Zhe; Cui, Di (International Journal of Agricultural and Biological Engineering, 2022)
Firmness is one of the important indices to evaluate the internal quality of fruit. In this study, a noncontact loudspeaker-based detection system was developed to evaluate apple firmness. The structural parameters of the excitation device were modified in the single-factor experiments, and the best combination of structural parameters was that the inner diameter of the gasket was 40 mm; the distance between fruit surface and loudspeaker was 95 mm. Besides, the proper posture style was that the apple was placed with its stem upward. After the modification of the Laser Doppler Vibrometer (LDV) method, the vibration response signals of 48 apples were measured to establish the firmness prediction model. The results showed that the better prediction performance of stiffness was obtained in multiple models. The Back Propagation Neural Network (BPNN) model had the best prediction performance by using parameters of elasticity index (EI), the peak value at the second resonance frequency f2(A2), and peak area S, with a correlation coefficient of prediction (rp) of 0.914; root mean square error of prediction (RMSEP) of 0.491 N/mm. Therefore, the proposed detection system is feasible to nondestructively detect apple firmness, which has the potential to be applied in online detection.Keywords: fruit firmness, excitation device, structural parameters, vibration parametersDOI: 10.25165/j.ijabe.20221501.7028Citation: Ding C Q, Wang D C, Feng Z, Cui D. Detection of apple firmness with a novel loudspeaker-based excitation device. Int J Agric & Biol Eng, 2022; 15(1): 260–266.